Religious Plurality and Deversity in Australia and Its Common Issues - M. Amin Nurdin (Refleksi, 2000)
All non-Aboriginal religious groups have found their way to Australia by migration either by being carried by migrating peoples or by migrating as systems of belief and practice transmitted by means of of teachers, publications or missionaries.